Causes of Morbidity and Mortality among the Neonates Admitted to theNeonatal Intensive Care Unit in a Rural Area of Bangladesh (The Planet, 2024)
Introduction: Neonates are highly vulnerable to various health challenges. This period involves critical physiological adaptations necessary for survival outside the womb. Neonatal morbidity and mortality are significant public health concerns, especially in rural areas of developing countries like Bangladesh. This study aimed to assess the causes of morbidity and mortality among neonates admitted to the neonatal intensive care unit in a rural area of Bangladesh. Methods & Materials: This retrospective cross-sectional study was conducted in the Neonatal Intensive Care Unit (NICU), Kumudini Women’s Medical College Hospital (KH), Tangail, Bangladesh from January to December 2023. We reviewed 2,777 records of neonates from a rural area of Bangladesh who received NICU care at the specified hospital. Purposive sampling was used for selection, and data analysis was performed with MS Office tools. Results: Of the 2,777 neonates, 75.19% recovered, 15.66% died, 14.55% were discharged on request, and 1.26% was referred. The major causes of death were prematurity (35.40%), perinatal asphyxia (28.74%) and neonates with respiratory distress (22.07%). For morbidity, notable conditions were PNA HIE II-III (25.56%), all preterm types (15.96%), neonates with respiratory distress (13.40%), meconium stain (13.36%), and neonatal jaundice (11.38%). Conclusion: The findings highlight the need to raise awareness about antenatal checkups, screen for high-risk pregnancies, promote institutional deliveries, and improve maternal health to prevent preterm labor and PNA. Enhancing NICU resources and treatment plans can significantly reduce deaths, infections, and discharge on-request rates.
Keywords: Causes of morbidity; Mortality; Neonates; Neonatal intensive care unit; NICU; Rural area